"Efecto in vitro de la desloratadina en daño oxidativo inducido en membranas mitocondriales de células hepáticas de rattus norvegicus var.albinus". - Altamirano Sarmiento, Dan Orlando (2014)
ABSTRACT The present work of investigation had as aim determine the effect in vitro of the desloratadina opposite to the lipoperoxidación induced in membranes mitocondriales of hepatic cells of Rattus norvegicus var. albins, there was in use the method of the TBARS (Species You Reactivate for the Acid Tiobarbitúrico). The animals of experimentation were 36, distributed randomly in three groups, (a control and two problems), the doses of test were of 13 and 26 μM. The isolation of the hepatic mitocondrias, it was realized by Rickwood's method and cols, being in use Succinato Deshidrogenasa's biochemical method, for the identification mitocondrial. After the exhibition to the medicine, the induction of the lipoperoxidación was realized in membranes mitocondriales, and one determined the concentrations of malondialdehído. The results were that alone the concentration of 26μM (0.665 nmol MDA/g liver) I present protective effect to the stress oxidatívo induced, on having compared it with the group of 13μM (0.797 nmol MDA/g liver), and group control (0.861 nmol MDA/g liver).